2003
DOI: 10.1039/b302092d
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective recognition of a chiral quaternary ammonium ion by C3 symmetric cyclic hexapeptides

Abstract: C3 Symmetric cyclic hexapeptides containing alternating L-proline and 3-aminobenzoic acid derivatives as subunits possess different affinities towards the two enantiomers of the N,N,N-trimethyl-1-phenylethyl ammonium cation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In a second study it was shown, that these cyclic peptides show enantiodiscrimination properties [747]. The best two examples, 233e and 233f , distinguish the two enantiomers of N , N , N -trimethyl-1-phenylethyl ammonium picrate in 0.1% DMSO–CDCl 3 with K R /K S = 1.5.…”
Section: Reviewmentioning
confidence: 99%
“…In a second study it was shown, that these cyclic peptides show enantiodiscrimination properties [747]. The best two examples, 233e and 233f , distinguish the two enantiomers of N , N , N -trimethyl-1-phenylethyl ammonium picrate in 0.1% DMSO–CDCl 3 with K R /K S = 1.5.…”
Section: Reviewmentioning
confidence: 99%
“…Solutions of salts [Bu 3 NH][L-22] in CHCl 3 or [cinchonidinium][D-22] in 7.5-10% DMSO/CHCl 3 were prepared (1 equiv.) and added to orange-coloured solutions of racemic [55]Cl 2 or [57]Cl 2 in water (1 equiv.). Upon vigorous stirring of the biphasic mixtures, a partial transfer of coloration occurred from the aqueous layers to the organic ones (Fig.…”
Section: By Asymmetric Extractionmentioning
confidence: 99%
“…Ion pairing of this cation with racemic 22 improves the binding affinity in CHCl 3 by a factor of ~3 over picrate. 57 Fontecave and co-workers have been able to resolve the cis-[Ru(dmp) 2 (CH3CN) 2 ] complex (dmp = 2,9-dimethyl-1,10-phenanthroline) using D-22 as counterions. This "chiralat-metal" ruthenium derivative was then used as a catalyst for the oxidation of sulfides to sulfoxides by hydrogen peroxide.…”
Section: Addendummentioning
confidence: 99%
“…[1,2] Concave receptor structures with rigidly oriented or conformationally locked functional groups are therefore among the most potent systems for molecular recognition. [3][4][5][6][7][8][9][10][11][12][13][14] Since many target molecules for sensors exhibit C 3 or pseudo-C 3 symmetry, complementary scaffolds with threefold symmetry are popular. [15] An unusual large and rigid backbone providing concave and convergent preorganized functional groups for supramolecular interaction was established by us recently.…”
Section: Introductionmentioning
confidence: 99%